Стійкість функціонування підприємства як економічної системи - Замкевич, Б.М. (Культура народов Причерноморья, 2013)
В економіці термін стійкості прийнято розглядати як категорію, яка характеризує конкретні форми проявлення системи (стан, розвиток, фінанси, використання ресурсів і т. п.). В сучасному розумінні стійкість підприємства, як економічної системи, є функціонально обмеженим параметром. На підставі аналогії термодинамічних і економічних процесів, другого закону термодинаміки запропоновано критерій оцінки стійкості підприємства (економічної системи) як величину обернену до зміни його ентропії, який характеризує степінь стійкості системи протистояти кризовим процесам. В экономике категорию стойкости принято рассматривать как категорию, которая характеризует конкретные формы проявления системы (состояние, развитие, финансы, использование ресурсов и т. п.). В современном понимании стойкость предприятия, как экономической системы, является функционально ограниченным параметром. На основании аналогии термодинамических и экономических процессов, второго закона термодинамики предложен критерий оценки стойкости предприятия (экономической системы) как величина обратная к изменению его энтропии, который характеризует степень стойкости системы противостоять кризисным процессам. To realize the main strategic directions of economic policy in providing a country safety is impossible without the proof and competitive real sector of economy. Taking it into account, the special attention is paid to such category as “stability”. In economics it is accepted to study this term as a subjective category which characterizes the specific forms of the system (state, development, funds, resources allocation). Replacing many parameters of enterprise financial activity with a coefficient of the system stability will do this process simpler and more correct. On the basis of an analogy of thermodynamic and economic processes, the criteria of enterprise stability are suggested. According to the second law of thermodynamics, entropy of an isolated system with irreversible changes increases. In any economic system the real or irreversible changes take place. Any system processes continues until there is a balance. An economic system with real irreversible changes is developing in the direction of maximal stability or in the direction of complete degradation. It determines a natural deliberate motion which is not organized according to the system, for example, an agricultural enterprise moves towards bankruptcy or liquidation. Such state of the system is maximally proved. It means that the value connected with the entropy change of the economic system characterizes the degree of the system stability to withstand against the crisis. It is suggested to apply this value as a criterion of the system stability and to name it as a “coefficient of the system stability”.